Effect of forming techniques on efficiency of tubular oxygen separating membranes. Issue 1 (January 2017) - Gromada, Magdalena; Trawczyński, Janusz; Wierzbicki, Michał; Zawadzki, Mirosław
Abstract: Two dense thin-walled tubular membranes used to separate oxygen from air manufactured from a Ba0.5 Sr0.5 Co0.8 Fe0.2 O3−δ (BSCF) mixed oxide with perovskite-like structures were synthesized by both extrusion and isostatic pressing methods. The properties of the sintered membranes (the apparent density, the apparent porosity, the water absorbability, the chemical composition, the crystallographic structure and microstructure, and the oxygen mobility) that affect oxygen permeation through the membranes were determined. Both manufactured membranes were capable of separating oxygen from air. The highest oxygen permeation flux (2.33 cm 3 O2 /(cm 2 min)) was obtained using the membrane synthesized by extrusion at 950 °C under 2 dm 3 /min air flow and 5 dm 3 /min of helium flow. The effect of the pressure used during the synthesis of the membranes on the properties of the membranes is discussed. The influence of air quantity delivered to the system on the oxygen permeation flux for both membranes at 950 °C and constant helium flow was also determined. Extrusion was found to be an attractive method to manufacture industrial-scale membranes that separate oxygen from air.